Alcaloides β-carbolínicos: interação com DNA (Calf thymus), proteína de soro bovino (BSA), correlação com atividade biológica e Docking molecular - Pereira, Karlly Thayanny de Oliveira (2018)
The alkaloids derived from the β-carbolines have several biological activity, being their greater prominence attributed the anticancer activities. This property, therefore, has aroused the interest of the synthetic chemists in the search of new prototypes to the anticancer drugs. However, the design of more promising drugs requires information that can be obtained from the study of the interaction of these small molecules with DNA and BSA protein. This is because DNA is the main target of several drugs, including anticancer drugs, while BSA is the multi-drug Carrier protein, which influences their effectiveness. For this reason, the study of the interaction of small molecules with these macromolecules has been advancing in recent decades. In this context, the objective of the present study was to evaluate the interaction of β-carbolinic alkaloids with ctDNA (Calf thymus) and also with the bovine serum albumin (BSA) protein, by means of absorption spectroscopy techniques in UV-visible and molecular fluorescence. The results showed that there was interaction of the compounds derived from β-carbolinic alkaloids with the two macromolecules evaluated, ctDNA and BSA, resulting in the formation of nonfluorescent supramolecular complexes through the static quenching mechanism. In the study with ctDNA, it was observed that the interaction of the compounds with the macromolecule was significant, with values of the binding constants, Kb, ranging from 2.45×104 to 1.18×106 L mol-1, reaction performed in the ratio of 1:1 (compound: ctDNA). The highest Kb value was exhibited by compound 9c, which has an N,N-dimethylaniline group at the C1 position in the β-carboline ring, whereas for compound 9e, having the substituent at C1 o-chlorophenyl, showed the lowest value of Kb. The main mode of interaction occurs preferentially via intercalation, which was established by potassium iodide (KI) and ethidium bromide (EB) assays. From the study of the analytical correlation between the values of Kb vs IG50, it was possible to observe that the intercalation mode, for some compounds, is the main mechanism of anticancer action of the same. Correlation was therefore found for colon (HT-29) strains, for compounds 9e, 10b, 9c; and kidney (786-0) for compounds 9e, 17 and 9c. For the study with the BSA protein, the Kb values ranged from 3.2×104 to 4.1×106 L mol-1, the highest value corresponding to 9e, shown a good affinity with the protein and, with a stoichiometric ratio of 1:1. Finally, it was observed by molecular docking that the compounds studied have good affinity with a hydrophobic cavity contained in the site I of the protein, located in subdomain IIA where the tryptophan (Trp213) residue is found. Thus, it is possible to state that the bioactive compounds evaluated, derived from β-carbolines, have an affinity with both DNA and BSA protein.